CDK inhibitors from past to present: A new wave of cancer therapy. (January 2023) - Mughal, Muhammad Jameel; Bhadresha, Kinjal; Kwok, Hang Fai
Abstract: Deregulation of the cell cycle machinery, which has been linked to dysregulation of cyclin-dependent kinases (CDKs), is a defining characteristic of cancer, eventually promoting abnormal proliferation that feeds tumorigenesis and disease development. In this regard, several CDK inhibitors (CDKIs) have been developed during the last few decades (1st, 2nd, and 3rd generation CDKIs) to inhibit cancer cell proliferation. 1st and 2nd generation CDKIs have not received much clinical attention for the treatment of cancer patients because of their limited specificity and high toxicity. However, the recent development of combination strategies allowed us to reduce the toxicity and side effects of these CDKIs, paving the way for their potential application in clinical settings. The 3rd generation CDKIs have yielded the most promising results at the preclinical and clinical levels, propelling them into the advanced stages of clinical trials against multiple malignancies, especially breast cancer, and revolutionizing traditional treatment strategies. In this review, we discuss the most-investigated candidates from the 1st, 2nd, and 3rd generations of CDKIs, their basic mechanisms of action, the reasons for their failure in the past, and their current clinical development for the treatment of different malignancies. Additionally, we briefly highlighted the most recent clinical trial results and advances in the development of 3rd generation FDA-approved selective CDK4/6 inhibitors that combat the most prevalent cancer. Overall, this review will provide a thorough knowledge of CDKIs from the past to the present, allowing researchers to rethink and develop innovative cancer therapeutic regimens. Graphical Abstract: The progression of the cell cycle depends heavily on CDKs, and dysregulation of CDKs has been linked to cell cycle deregulation and aberrant proliferation, which are the two key hallmarks of cancer cells. Multiple CDKIs have been developed in past few decades to inhibit cancer cell proliferation. Early generation CDKIs displayed exceptional anticancer activity, but their significant toxicity and limited selectivity cast doubt on their therapeutic use. 3rd generation CDKIs, on the other hand, have yielded the most promising clinical results with relatively low toxicity and high specificity, propelling them into the advanced stages of clinical trials against multiple malignancies, particularly against breast cancer, and revolutionizing traditional treatment strategies. ga1